Smartphone for Next Generation Attendance System and Human Resources Payroll System - Benfano Soewito; Fergyanto E. Gunawan; Manik Hapsara (IAES Indonesia Section, 2017)
A wide variety of current attendance system can be found easily in the market, but there are still some deficiencies in the attendance system; how the company will control employees are outside the office building and how employees can take ad- vantage of the attendance system to view a variety of information needed. The modern attendance system must integrated with a human resources management and payroll system. Others issues with current attendance system, beside could not control the staff who work outside the office are conventional attendance system that spends a lot of paper and a long process due to be entered manually into the system for processing payroll, while the electronic attendance system with limited device can cause queues at the time employee entry and exit the office building. In this work, we introduce online attendance system on mobile devices and is integrated with the payroll system. It is a system created to overcome some of the limitations that occur in manual or electronic attendance system which is often conventionally used today. We utilized Global Positioning System (GPS), microphone, and fingerprint scanner that available on a smartphone or others mobile devices. We developed our application base on android platform because the android is the most platforms that have been using in the most mobile devices. Using our proposed methodology, the employee can do attendance using their mobile devices and the do not need to be in queue and the employee who work outside the office also can do the attendance. Our research showed that our proposed methodology can used for the next generation absence system.